Analisis integrasi aspek keterampilan proses sains (KPS) dalam buku teks pelajaran fisika sma kelas X semester 2 - Febrian Virijai; Asrizal A; Desnita D (Universitas Negeri Padang, 2020)
Science Process Skills (KPS) are skills that facilitate learners discover facts, determine concepts and apply theories in everyday life. In fact in the KPS implementation class is still low. In addition to the low implementation of KPS, the textbooks used by high schools in West Sumatra have not yet known the value of KPS. The solution to this problem is knowing which books have high KPS that will be used in the teaching and learning process.This study aims to determine the value of KPS in Physics textbooks used by high schools in West Sumatra. This research is a descriptive study with a qualitative approach. The study population is all physics textbooks for Class X Semester 2 used in West Sumatra. The research sample is the four most books used in West Sumatra High School. The research instrument used has a high validity value. This research instrument uses 10 PPP components which are broken down into 37 PPP indicators.The results obtained that the book used in the classroom as a source of learning for students has 1 sample of books whose KPS scores are in the